Using Measured Values in Bell's Inequalities Entails at Least One Hypothesis in Addition to Local Realism - Hnilo, Alejandro Andrés (2017)
The recent loophole-free experiments have confirmed the violation of Bell?s inequalities in nature. Yet, in order to insert measured values in Bell?s inequalities, it is unavoidable to make a hypothesis similar to ?ergodicity at the hidden variables level?. This possibility opens a promising way out from the old controversy between quantum mechanics and local realism. Here, I review the reason why such a hypothesis (actually, it is one of a set of related hypotheses) in addition to local realism is necessary, and present a simple example, related to Bell?s inequalities, where the hypothesis is violated. This example shows that the violation of the additional hypothesis is necessary, but not sufficient, to violate Bell?s inequalities without violating local realism. The example also provides some clues that may reveal the violation of the additional hypothesis in an experiment.